Population and clonal structure of Acropora cf. hyacinthus to inform coral restoration practices on the Great Barrier Reef - Lorna Howlett; Emma F. Camp; Nicolas S. Locatelli; Iliana B. Baums; Paige Strudwick; Sage Rassmussen; David J. Suggett (Coral Reefs, 2024)
A key goal of coral restoration is to re-establish self-sustaining coral populations and ensure resilience to future stressors, which requires that genetic diversity is maximised. However, coral genetic and genotypic (clonal) diversity is variable across reef sites via success of sexual recruitment, and cryptic species diversity can complicate breeding efforts. Assessing genotypic and genetic diversity of colonies to be used in restoration is therefore critical to avoid founder, inbreeding or outbreeding effects. Considering recent efforts to upscale coral propagation on the Great Barrier Reef (GBR), we examined species, population and clonal structure of a commonly out-planted tabular Acropora species— Acropora hyacinthus (Dana, 1864). A total of 189 colonies were sampled from six reef systems throughout the northern-central GBR and genotyped using an Acropora- specific Affymetrix microarray, which resulted in 1387 variant sites that passed quality control. Cryptic species were readily resolved and all sampled A. hyacinthus colonies represented unique genotypes within sites at three reefs. At reefs that contained multi-ramet genets (clonal genotypes), the mean and maximum between-ramet distances were 0.68 and 1.99 m, respectively. Therefore, sampling colonies > 2 m apart increases the likelihood these colonies represent distinct genets. Such a sampling design therefore maximises genotypic diversity when sourcing colonies for propagation and out-planting. Based on these variant sites, we found no between-reef genetic divergence based on locality. Furthermore, through unintentional sampling of non-target tabular Acroporid species, we show how this genotyping method may be used for resolving taxonomic uncertainty as well as population dynamics.

Experience-dependent tuning of the olfactory system - Nicolás Pírez; Martín Klappenbach; Fernando F Locatelli (Current Opinion in Insect Science, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Scientometric analysis and literature synthesis of 60 years of science on the Atlantic goliath grouper ( Epinephelus itajara ) - Anna C. P. Locatelli; Rodrigo F. Bastos; Matheus A. Oliveira; Beatrice P. Ferreira (Journal of Fish Biology, 2023)
Here, the authors investigate the evolution of scientific literature on the Atlantic goliath grouper ( Epinephelus itajara ), the largest grouper species in the Atlantic. This species was considered threatened according to the IUCN for nearly three decades due to overfishing and has been protected from fishing in a large part of its range. For the purpose of evaluating the scientific production on an endangered species banned from fishing, the authors present a scientometry and synthesis review analysing the literature produced in the timeline and the content of their studies. To this end, they set up an almost 60‐year literary database through the Scopus, Web of Science and Google Scholar platforms. They analyse the publication and knowledge area patterns over the time in the world and in Brazil. They also feature the main areas, locations, ecosystems and types of those research studies and briefly describe the main records found in each decade. An increase in the number of publications was observed from the 1990s onwards worldwide, and particularly in Brazil from the 2000s, coinciding with the pioneering legislations for species protection. Most of the studies were classified within ecology and conservation and took place in countries that implemented moratoriums and had extensive areas of mangroves. Thus, fishing moratorium, classification as endangered, mangroves distribution and conservation all play a role in the studies distribution and contribute positively to the knowledge, as well as support conservation strategies for the species and its ecosystems of occurrence.

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.

Breaking the ecosystem services glass ceiling: realising impact - Genevieve Patenaude; Sven Lautenbach; James S. Paterson; Tommaso Locatelli; Carsten F. Dormann; Marc J. Metzger; Ariane Walz (Regional Environmental Change, 2019)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

A porcine circovirus-2 mutant isolated in Brazil contains low-frequency substitutions in regions of immunoprotective epitopes in the capsid protein - Rafael Locatelli Salgado; Pedro Marcus Pereira Vidigal; Natalia F. Gonzaga; Luiz F. L. de Souza; Marcelo D. Polêto; Thiago Souza Onofre; Monique R. Eller; Carlos Eduardo Real Pereira; Juliana L. R. Fietto; Gustavo C. Bressan; Roberto M. C. Guedes; Márcia R. Almeida; et al. (Archives of Virology, 2015)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Determination of Antibiotics in Brazilian Surface Waters Using Liquid Chromatography–Electrospray Tandem Mass Spectrometry - Marco Antonio F. Locatelli; Fernando F. Sodré; Wilson F. Jardim (Archives of Environmental Contamination and Toxicology, 2011)

Occurrence of Emerging Contaminants in Brazilian Drinking Waters: A Sewage-To-Tap Issue - Fernando F. Sodré; Marco Antonio F. Locatelli; Wilson F. Jardim (Water, Air, & Soil Pollution, 2010)

Efficiency of transient transformation in tobacco protoplasts is independent of plasmid amount - F. Locatelli; C. Vannini; E. Magnani; I. Coraggio; M. Bracale (Plant Cell Reports, 2003)

Characterisation of cAMP-dependent protein kinase isoforms in the brain of the crab Chasmagnathus - F. Locatelli; C. LaFourcade; H. Maldonado; A. Romano (Journal of Comparative Physiology B, 2001)

Successful Treatment with Ampicillin and Fluoroquinolones of Human Endocarditis due to High-Level Gentamicin-Resistant Enterococci - M. F. Tripodi; A. Locatelli; L. E. Adinolfi; A. Andreana; R. Utili (European Journal of Clinical Microbiology & Infectious Diseases, 1998)